Physical properties of sunflower seeds during drying - Thaís Adriana de Souza Smaniotto (Semina: Ciências Agrárias, 2017)
The aim of this work was to determine the effect that the moisture content has on the physical properties of sunflower seeds. The cultivar Olisun 3, with an initial moisture content of 34.1 (% wb), was used and then subjected to drying in an oven with forced air ventilation under three temperature conditions: 40, 60 and 80 °C. The reduction in the moisture content during drying was monitored by the gravimetric method until it reached a final moisture content of 8.0 ± 1.0 (% wb). The physical properties were analysed: the bulk density, true density, intergranular porosity and volumetric shrinkage of the mass and unit and terminal velocity. The reduction in the moisture content influenced the physical properties of sunflower seeds and caused a decrease in the intergranular porosity, bulk density and true density at all examined temperatures. The mass and volumetric contractions of the unit and reduction in shrinkage rates all increased with the drying of sunflower seeds at all studied temperatures. The terminal velocity increased as the moisture content of the grains increased, which was more evident at the drying temperature of 80 °C.